Pengaruh Tepung Cacing Sutra (Tubifex sp) Dan Pelet Komersial Yang Dikombinasi, Terhadap Pertumbuhan Dan Kelangsungan Hidup Ikan Bandeng (Chanos chanos) - Gradiana Rany Seran; Nicodemus Dahoklory; Asriati Djonu (Nusa Cendana University, 2026)
Silkworm flour is a natural ingredient, which has a high protein content that is suitable as a combination ingredient for milkfish feed. The purpose of this study was to determine the effect of providing a combination of silkworm flour (Tubifex sp) and commercial pellets on the growth and survival of milkfish (Chanos chanos). This study was conducted in the milkfish pond of Fahiluka Village, Central Malaka, East Nusa Tenggara for 60 days using a Completely Randomized Design (CRD) with 5 treatments and 2 replications. Treatments consisted of A (100% pellets), B (25% silkworm flour + 75% pellets), C (50% silkworm flour + 50% pellets), D (75% silkworm flour + 25% pellets), and E (85% silkworm flour + 15% pellets). The parameters observed in this study included absolute weight growth, specific daily growth (SGR), survival rate, and water quality. The results of this study indicate that treatment E produced the highest absolute weight gain (18.45 g), significantly different (p<0.05) compared to other treatments. The survival rate of the study reached 100% in all treatments. Water quality measurements during the study were within the optimal range for milkfish growth. Therefore, the combination of 85% silkworm meal and 15% pellets is the best feed to increase milkfish growth without affecting its survival. Keywords: Chanos chanos, Survival, Feeding, Growth, Tubifex sp